Candida auris candidaemia in Indian ICUs: analysis of risk factors. (20th February 2017) - Rudramurthy, Shivaprakash M.; Chakrabarti, Arunaloke; Paul, Raees A.; Sood, Prashant; Kaur, Harsimran; Capoor, Malini R.; Kindo, Anupma J.; Marak, Rungmei S. K.; Arora, Anita; Sardana, Raman; Das, Shukla; Chhina, Deepinder; et al.
Abstract : Objectives: To identify the risk factors associated with Candida auris candidaemia, as this fungus now poses a global threat. Methods: We performed a subgroup analysis of a previously reported study of 27 Indian ICUs. The clinical data of candidaemia cases due to C. auris and other Candida species were compared to determine significant risk factors associated with C. auris infection. Results: Of the 1400 candidaemia cases reported earlier, 74 (5.3%) from 19 of 27 ICUs were due to C. auris . The duration of ICU stay prior to candidaemia diagnosis was significantly longer in patients with C. auris candidaemia (median 25, IQR 12–45 days) compared with the non- auris group (median 15, IQR 9–28, P  <   0.001). Based on logistic regression modelling, admission to north Indian ICUs [OR 2.1 (1.2–3.8); P  =   0.012], public-sector hospital [OR 2.2 (1.2–3.9); P  =   0.006], underlying respiratory illness [OR 2.1 (1.3–3.6); P  =   0.002], vascular surgery [OR 2.3 (1.00–5.36); P  =   0.048], prior antifungal exposure [OR 2.8 (1.6–4.8); P  <   0.001] and low APACHE II score [OR 0.8 (0.8–0.9); P  =   0.007] were significantly associated with C. auris candidaemia. The majority (45/51, 88.2%) of the isolates were clonal. A considerable number of isolates were resistant to fluconazole ( n  =   43, 58.1%), amphotericin B ( n  =   10, 13.5%) and caspofungin ( n  =   7, 9.5%). Conclusions: Although C. auris infection has been observed across India, the number of cases is higher in public-sector hospitals in the north of the country. Longer stay in ICU, underlying respiratory illness, vascular surgery, medical intervention and antifungal exposure are the major risk factors for acquiring C. auris infection even among patients showing lower levels of morbidity.